2021
DOI: 10.3389/fcimb.2021.685861
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Bovine Digital Dermatitis Microbiota Reveals Distinct Microbial Community Structures Associated With Lesions

Abstract: Bovine digital dermatitis (DD) is a significant cause of infectious lameness and economic losses in cattle production across the world. There is a lack of a consensus across different 16S metagenomic studies on DD-associated bacteria that may be potential pathogens of the disease. The goal of this meta-analysis was to identify a consistent group of DD-associated bacteria in individual DD lesions across studies, regardless of experimental design choices including sample collection and preparation, hypervariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
1
15
0
4
Order By: Relevance
“…Most feet were positive for Fusobacterium at multiple timepoints, including samples from mock inoculated and from samples obtained prior to inoculation with lesion material (week 0). While Fusobacterium is a known contributor to foot rot of cattle and small ruminants, its role in DD is not well defined and is controversial ( 11 , 41 , 48 54 ). Our data supports an ambiguous role for Fusobacterium in TAHD as most sheep feet, even in the mock inoculated treatment group, were positive for Fusobacterium prior to inoculation and many in the control group did not develop lesions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most feet were positive for Fusobacterium at multiple timepoints, including samples from mock inoculated and from samples obtained prior to inoculation with lesion material (week 0). While Fusobacterium is a known contributor to foot rot of cattle and small ruminants, its role in DD is not well defined and is controversial ( 11 , 41 , 48 54 ). Our data supports an ambiguous role for Fusobacterium in TAHD as most sheep feet, even in the mock inoculated treatment group, were positive for Fusobacterium prior to inoculation and many in the control group did not develop lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing mock to inoculated tissues at three timepoints, 86 OTUs were increased in inoculated samples with the majority found in all three sampling (43 OTUs) timepoints but the highest number was found at week 2 ( Figure 7 ). Others have reported that microbial diversity of DD lesions decreases with time, with treponemes eventually becoming the dominant organism ( 31 , 41 , 44 , 57 ). This was not observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При развитии болезни из пораженных мест выделяется большое разнообразие микроорганизмов [3,6]. По данным авторов [5] такие бактерии как трепонемы, микоплазмы, порфиромонады и/или фузобактерии могут играть ключевую роль в патогенезе пальцевого дерматита.…”
Section: Introductionunclassified
“…По разным литературным источникам частота встречаемости пальцевого дерматита может достигать до 80% среди поголовья крупного рогатого скота. Чаще распространенность данной болезни составляет около 20% в стаде [1,3,5].…”
Section: Introductionunclassified